HUBUNGAN DUKUNGAN PETUGAS KESEHATAN, DUKUNGAN KELUARGA DAN PENGETAHUAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF - Metrianah; Fika Minata; Rizki Amalia; Sendy Pratiwi Rahmadhani; Rohaya (LPPM STIKes Mitra Adiguna, 2023)
ABSTRACT The Government's efforts to support the increase in exclusive breastfeeding have resulted in agreements or various recognitions, both globally and nationally, which aim to protect, promote, and support breastfeeding. It is hoped that every baby has the right to get exclusive breastfeeding and every mother can give breast milk. This is in line with the Sustainable Development Goals (SDGs) of the three second targets, namely by 2030, ending preventable infant and under-five mortality, with all countries trying to reduce neonatal mortality to at least 12 per 1000 live births. This study aims to determine the relationship between health worker support, family support and mother's knowledge with exclusive breastfeeding in the working area of ​​the Muara Enim Health Center, Muara Enim City in 2022. The method in this study used a cross sectional with a population of 467 respondents and a sample of 82 respondents. Data analysis used chi square statistical test with p value value (0.05). The results of this study of 49 respondents who received positive support with exclusive breastfeeding were 29 people (59.2%%) with p value = 0.002, of 31 respondents who received positive family support with exclusive breastfeeding were 19 people (61.3% ) p value = 0.02, meanwhile, from 27 respondents who have good knowledge of exclusive breastfeeding, 19 people (70.4%) p value = 0.002. Midwives are expected to increase counseling and socialize the exclusive breastfeeding program to the community.